HUBUNGAN PACARAN DENGAN PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR MAHASISWA STKIP WIDYA YUWANA MADIUN - Priska Rabu; Ola Rongan Wilhelmus (Bahasa Indonesia, 2018)
Courtship is a relationship that is be lived when a man and woman to each other like each other and want to live a more serious relationship. Courtship is a process whereby a person learn give and take, it means learning to give and accept each other and learn Build an Attitude of responsibility. Demanding challenges experienced person should manage themselves, bring a sense of independence responsibility and manhood. Motivation to learn can come from yourself, your family and a close friend (boyfriend) and friends. While the achievement is a result of the efforts of the work that has been achieved. Learning achievement is an attainment or results of operations of the acquired learning as learning activities. Courtship positive impact on motivation to learn is towards the availability of mutual support and encouragement, especially in terms of learning. When not assisting or encouraging it would weaken the motivation tolearn. While a courting positive impact on learning achievement is can obtain better results or maximum because they can help each other and compete fairly interms of learning. This research used a qualitative approach, the research data is done through a method of interviewing couples who are dating. Data analysis is done in three steps: data reduction, data presentation and verification of data. Results of the research revealed that 75% of respondents said courting as an intimate relationship between man and woman know each other in depth. The results also showed that 75% of respondents said that the positive impact of a boyfriend is encourage to improve motivation and learning achievement. Following the 50,2% of respondents said that courting to make the couple feel lazy to learn because it always uses a lot of time for dating.